PENGARUH PELATIHAN, PENGEMBANGAN PROFESI, DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA PERWAKILAN BPKP PROVINSI JAWA TIMUR - Dwiantoro, Anton; Purwanto, Purwanto; Sari, Anita Kartika (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the effects of training, professional development, and competence on employee performance at the East Java Representative Office of BPKP. A quantitative approach with a causal associative design was employed. The population and sample consisted of 208 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS. The results show that training has a positive and significant effect on employee performance (B = 0.574; t = 11.265; p < 0.001), professional development has a positive and significant effect on employee performance (B = 0.298; t = 7.885; p < 0.001), and competence has a positive and significant effect on employee performance (B = 0.648; t = 10.561; p < 0.001). Simultaneously, the three variables significantly affect employee performance (F = 188.812; p < 0.001). The adjusted R-squared value of 0.731 indicates that the research model explains 73.1% of the variation in employee performance. Training is the most dominant variable, with a standardized beta value of 0.444. These findings emphasize the importance of managing training, professional development, and competence in an integrated manner to improve employee performance